Social media research trends in Malaysia: an analysis of three major communication journals in Malaysia - A. Rahman, Nur Atikah; Hassan, Md. Salleh (2015)
The emergence of social media such as blogs and microblogs; social networking sites; virtual game world; collaborative projects; content communities and virtual social world have garnered millions of users in Malaysia. With the development of social media, the academic and media environment have shown tremendous changes in mass communication research, leading to increasing numbers of research on social media. Hence, this quantitative study aspires to discuss various issues related to social media by tracing the research trends in Malaysia. Data were gathered through content analysis by reviewing social media research articles in three major communication academic journals in Malaysia such as Malaysian Journal of Media Studies (Jurnal Pengajian Media Malaysia), Malaysian Journal of Communication (Jurnal Komunikasi) and Global Media Journal-Malaysian Edition during a ten-year period. Findings on research topics, research methodology and theoretical frameworks were identified. Comparisons of data between the early emergence of social media (2004-2008) and current era of social media (2009-2014) were also made. The results of the study provided insights for researchers and practitioners into the patterns and issues associated with social media in the country.